Indian Corporate Social Responsibility: From philanthropy to assessing the sustainability of business and society - Gilormini, Patrick (Management and Administration Journal, 2024)
India Corporate Social Responsibility (CSR) has undergone significant changes in the past three years. Their driving factors are regulations and financial institutions requirements: the National Voluntary Guidelines on Social, Environmental & Economic Responsibilities of Business [2011], the Security Exchange Board of India clause 55 [2012] and the New Company Act section 135 [2013]. Indian CSR appears essentially about what is done with corporation profits. It means engaging directly with local communities, identifying their basic needs and integrating them with business goals. The top major themes area for Indian CSR initiatives are community welfare, education, health care and rural development. This chapter presents the historical tradition of CSR as corporate philanthropy in India. After a presentation of the new legal framework and recent institutional developments, it analyses their implication on CSR reporting and organizational challenges for Indian companies especially SMEs.